1997
DOI: 10.1046/j.1365-2168.1997.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of different insufflation pressures for laparoscopic cholecystectomy

Abstract: Insufflation pressure significantly affects the haemodynamic changes and postoperative pain associated with laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 7 publications
2
52
1
2
Order By: Relevance
“…Some studies have also shown that the shoulder tip pain is minimal if the initial insufflation rate is kept suboptimal, although this needs to be substantiated. Some studies have shown that the incidence and intensity of postoperative shoulder tip pain was significantly less in the low-pressure pneumoperitoneum group when compared with standard-pressure pneumoperitoneum groups [8,[11][12][13][14][15][16]. Our study, however, shows that the incidence of shoulder pain has no statistical difference between groups undergoing laparoscopic surgery at different pneumoperitoneal pressures.…”
Section: Discussioncontrasting
confidence: 72%
“…Some studies have also shown that the shoulder tip pain is minimal if the initial insufflation rate is kept suboptimal, although this needs to be substantiated. Some studies have shown that the incidence and intensity of postoperative shoulder tip pain was significantly less in the low-pressure pneumoperitoneum group when compared with standard-pressure pneumoperitoneum groups [8,[11][12][13][14][15][16]. Our study, however, shows that the incidence of shoulder pain has no statistical difference between groups undergoing laparoscopic surgery at different pneumoperitoneal pressures.…”
Section: Discussioncontrasting
confidence: 72%
“…The fall in cardiac index lasted longer (7 vs 2 minutes) and coincided with a slower rise in mean arterial pressure in the group with higher insufflation pressure. The authors felt that the hemodynamic effects of carbon dioxide are overshadowed by the mechanical effects of increased intra-abdominal pressure during laparoscopy [8]. Dexter et al found a moderate increase in heart rate after peritoneal insufflation which reached statistical significance for the high pressure group.…”
Section: Discussionmentioning
confidence: 96%
“…Only a few studies have dealt with comparison of cardiopulmonary parameters at different pressures of PP [7,8,12,20,21]. Wallace et al in a prospective, randomized doubleblinded study of 40 patients showed that there were no significant differences in intraoperative heart rate or cardiac index, although the latter fell significantly soon after insufflation in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some study define 'normal' insufflation pressure as 12-15 mmHg and a 'low' pressure as 5-7 mmHg [21] while a recent review arbitrarily considered anything less than 12 mmHg as low pressure [33]. Studies in healthy individuals have shown less pronounced decrease in cardiac index using low pressure peritoneal insufflation, while the pulmonary parameters have remained more or less similar in both the groups [13,34,35]. By and large, the low pressure groups have also reported less post-operative pain and diminished analgesic requirement, but such was always not the case [34].…”
Section: Discussionmentioning
confidence: 99%